AN ANALYSIS OF THE SIXTH SEMESTER STUDENTS’ MIXING CODE BETWEEN AMERICAN ENGLISH AND BRITISH ENGLISH AT ENGLISH EDUCATION STUDY PROGRAM OF UNIVERSITAS PASIFIK MOROTAI - Safril Karie Safril Karie; Balqis Husain (Journal of English Education and Linguistics, 2020)
This research aimed to find out the mixing code between American English and British English as well as the language mixing code factors performed by English students of the third year at Universitas Pasifik Morotai. The method used to analyze the data in this study was the descriptive analysis method to clarify. This study showed that the English department of the third year Universitas Pasifik Morotai performed mixing code vocabulary between American English and British English. The mixing code of the sixth-semester students is the outer mixing code. Students mix both languages and from all results of the respondents, which is more dominant to the American accent, with total vocabularies of 50 and British English 45 vocabularies. . Some reasons put forward by the students when they produce code-mixing, firstly the students want to build motivation in learning English. Secondly, code-mixing in the teaching process makes their utterance clearer when explaining so the listener could understand faster. Code-mixing in the class expresses her/his emotion or feeling to the listener. The last reason is sometimes she/he finds a word that has no representation in another language.